Beda Persepsi Dokter Puskesmas Integrasi dan Non Integrasi di Kabupaten Klaten terhadap Penderita Skizofrenia - Anisa Renang, Carla Marchira (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Mental disorder is a health problem commonly found in the community. Studies showed that mental disorder often undetected and not well managed in primary care. Primary care doctors perception towards severe mental disorder i.e. schizophrenia will influence the management of this disorder.Objective: To identify different perception between integration and non-integration primary care doctor in Klaten regency towards schizophrenia patient.Subject and Method: Subjects were primary care doctors in Klaten Regency. The figure of sample was 48. Data was collected using perception towards schizophrenia patient instrument. Data was analyzed with Chi-Square.Result: Data collection showed 75% primary care doctors stated that schizophrenia was a disease which could be recovered, 45.8% stated they did not like to treat schizophrenia patient, 83.3% stated that schizophrenia patient needed to be supervised continuously, and 16.7% primary care doctors stated that schizophrenia patient is dangerous; therefore they needed to be isolated. Chi-square test showed different perception between integration and non-integration primary care doctor towards recovery of schizophrenia patient (x²=7.759, p=0.005), using of new antipsychotic (x²=9,966, p=0,002), supervision of schizophrenia patient continuously (x²=12.448, p=0.00), giving diagnosis of schizophrenia (x²=5.828, p=0.016) and isolation of schizophrenia patient (x²=12.448, p=0.00).Conclusion: There’s a significant difference between integration and non-integration primary care doctor towards recovery of schizophrenia patient, using of new antipsychotic, supervision of schizophrenia patient continuously, giving diagnosis of schizophrenia, and isolation of schizophrenia patient.Keywords: perception, primary care doctor, schizophrenia